Differences in soil carbon fractions and microbial communities and their underlying mechanisms between assisted natural regeneration and plantation forests in subtropical China - Zhiqiang Ding; Zhijie Yang; Yusheng Yang (PLoS ONE, 2026)
Subtropical forests are critical to regional carbon cycling, yet the mechanisms by which forest management practices influence soil organic carbon (SOC) stability are not yet fully understood. This study assessed SOC fractions and microbial communities across four forest management types in southeastern China: secondary forest, assisted natural regeneration (ANR), and two monoculture plantations ( Castanopsis carlesii and Cunninghamia lanceolata ). We measured soil physicochemical properties, microbial biomass, and community composition, and used structural equation modeling (SEM) to identify the biotic and abiotic pathways regulating SOC dynamics. The results showed that ANR maintained SOC concentrations and microbial traits comparable to those of secondary forests, while significantly reducing labile carbon losses relative to monoculture plantations. At our site, ANR also exhibited higher fine-root input and richer understory cover than plantations, supporting microbially mediated LC retention and, ultimately, greater SOC stabilization. SEM identified two partially independent regulatory pathways: (1) aboveground litter inputs influenced soil pH, carbon:nitrogen ratio, and ammonium nitrogen. These changes promoted the conversion of labile carbon into recalcitrant carbon and increased total SOC. (2) fine root biomass enhanced labile carbon accumulation by increasing the abundance of Gram-positive bacteria. Recalcitrant carbon is conventionally considered a stable SOC component. However, the SEM identified no direct pathway of influence from recalcitrant carbon to total SOC. This finding underscores the central role of labile carbon in SOC stabilization in humid subtropical systems. These findings demonstrate that ANR mitigates carbon losses by enhancing microbially mediated carbon retention and reducing disturbance. This approach supports SOC preservation through improved litter dynamics and root–microbe interactions, providing insights for sustainable forest carbon management.